Cytoreductive Nephrectomy Combined With Sequential Targeted Therapy For Treating Multiple Bilateral Metastatic Renal Cell Carcinoma: A Case Report - Zheng, Wanxiang; Gao, Ming; Hou, Guangdong; Wei, Di; Yuan, Jiarui; Chen, Meihong; Dun, Xinlong; Zhang, Geng; Wang, Fuli; Liu, Fei; Wang, Yanzhu; Chen, Tao; et al. (Archives of Clinical and Medical Case Reports, 2020)
Targeted therapy is the standard treatment for advanced renal cell carcinoma that has been used extensively in the past decade. Sequential targeted therapy is an available choice for patients who develop drug resistance. However, it is debatable whether mammalian target of rapamycin inhibitor or another tyrosine kinase inhibitor should be used for sequential therapy after first-line anti-angiogenic drug treatment. In this study, we summarized the case report of a 51-year-old patient with advanced bilateral renal cancer who underwent tumor reduction surgery and sequential targeted therapy. First-line sunitinib, second-line everolimus, and third-line axitinib were given to this patient as part of a sequential therapy. The whole treatment process in details is described and discussed. The results indicate that cytoreductive nephrectomy combined with sequential targeted therapy is safe and effective in the treatment of multiple metastatic renal cell carcinoma. First-line sunitinib and subsequent axitinib may be a good choice for sequential therapy.